Kepemimpinan Pembelajaran Kepala SekolahSmp Negeri 2 Kaliwungu Kendal - WACHIDDIN, AGUS (2016)
ABSTRACT Agus Wachiddin. Q. 100 120 003. The Instructional Leadership of the Principal at SMP Negeri 2 Kaliwungu Kendal. Thesis. Educational Administration Magistrate, Postgraduate School of Muhammadiyah University of Surakarta. 2015. The objectives of the research are to describe: 1) the principal's leadership in applying visionary and situational leadership; 2) the principal's leadership in managing learning programs; and 3) the principal's leadership in creating learning community at SMP Negeri 2 Kaliwungu Kendal. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at SMP Negeri 2 Kaliwungu Kendal. The object of the research was the principal's leadership at SMP Negeri 2 Kaliwungu Kendal. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The data validation is done using continuous observation, data triangulation, and member check techniques. The research concludes that: 1) the principal's leadership in applying visionary and situational leadership at SMP Negeri 2 Kaliwungu Kendal is performed through various policies supporting the quality learning. It is done in pursuance of the school's vision as an effective school; 2) the principal's leadership in managing learning programs at SMP Negeri 2 Kaliwungu Kendal is performed through the improvement of teachers professionalism. It is done by providing motivation, competence enhancement through the training and incentives, and also by providing sanction for the indicipline teachers, and also equipped the school facilities; and 3) the principal's leadership in creating learning community at SMP Negeri 2 Kaliwungu Kendal is performed by doing the analysis on supporting and inhibiting factors involved in the improvement of learning quality enhancement. The inhibiting and supporting factors are in the form of internal and external factors.